The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-21381-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing in the Middle Eastern Qatari population identifies genetic associations with 45 clinically relevant traits

Abstract: Clinical laboratory tests play a pivotal role in medical decision making, but little is known about their genetic variability between populations. We report a genome-wide association study with 45 clinically relevant traits from the population of Qatar using a whole genome sequencing approach in a discovery set of 6218 individuals and replication in 7768 subjects. Trait heritability is more similar between Qatari and European populations (r = 0.81) than with Africans (r = 0.44). We identify 281 distinct varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…To gain insights into the genetic architecture of health and disease-related quantitative traits, we performed the first genome wide association studies of a list of 45 quantitative traits in 6,045 individuals from the Qatari population (Thareja et al, 2021). Several important findings of this comprehensive study include replication of multiple associations reported in Caucasian and Asian GWASs; uncovering differences in allele frequencies and LD patterns for replicated loci; and discovery of novel genetic associations mostly with variants common in the QGP but rare in other populations.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the genetic architecture of health and disease-related quantitative traits, we performed the first genome wide association studies of a list of 45 quantitative traits in 6,045 individuals from the Qatari population (Thareja et al, 2021). Several important findings of this comprehensive study include replication of multiple associations reported in Caucasian and Asian GWASs; uncovering differences in allele frequencies and LD patterns for replicated loci; and discovery of novel genetic associations mostly with variants common in the QGP but rare in other populations.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Thareja et al [28] performed genome-wide association tests to delineate risk variants for 45 clinically relevant traits using a discovery set of whole-genome sequences of 6218 Qatari individuals. The examined traits included two (namely anthropometry and lipid) of the four classes of metabolic traits examined in our study [4].…”
Section: Gwa Studies For Metabolic Traits On Arab Populationsmentioning
confidence: 99%
“…The same trait-variant associations among Qatar and Kuwait is highlighted with bold and italics in list of traits. Thareja et al [28] observed four GWA-identified association signals in the Qatari cohort relating to anthropometric traits at genome-wide significance, which he Qatari cohort relating to lipid traits at genome-wide significance, which included 22 identified in the Kuwaiti meta-analysis cohort [4]; 17 of these 22 associations were with the same exact lipid trait in the Kuwaiti cohort; of the remaining five, four were observed with related lipid traits; and one with a related metabolic trait (FPG).…”
Section: Gwa Studies For Metabolic Traits On Arab Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort, each sample was characterized by a disease severity code. The disease severity classes are defined as follows: 1) Asymptomatic/Paucisymptomatic, 2) Severe, 3) Critical/life-threatening [37]. We used this information to investigate if we could identify any contribution of the singleton burden of the prioritized genes to the classification.…”
Section: Wes Covid-19 Cohortsmentioning
confidence: 99%